Helminths infecting Dryadosaura nordestina (Squamata: Gymnophthalmidae) from Atlantic Forest, northeastern Brazil - Teixeira, A. A.M.; Silva, R. J. [UNESP]; Brito, S. V.; Teles, D. A.; Araujo-Filho, J. A.; Franzini, L. D.; Santana, D. O.; Almeida, W. O.; Mesquita, D. O. (De Gruyter, 2018)
We analyzed the patterns of infection by helminths in populations of the Gymnophthalmidae lizard Dryadosaura nordestina from three Atlantic Forest fragments in Northeast Brazil. Prevalence and mean intensity of infection by location showed the following results: ARIE Mata de Goiamunduba (60.8 % and 10.4 ± 8), RPPN Engenho Gargaú (83.3 % and 20.8 ± 19.7) and Benjamim Maranhaõ Botanical Garden (70.4 % and 7.78 ± 5.8). We provide the first records of helminth infection for the lizard D. nordestina, in which three species of nematodes, Aplectana sp., Cosmocerca sp. and Physaloptera lutzi and one trematode Haplometroides odhneri were recovered. Trematodes of the genus Haplometroides were previously known as parasites only in snake and amphisbaenian hosts in South America. Now, our study provides the first record of a species belonging to this genus parasitizing lizards. In conclusion, our study shows that D. nordestina have a depleted helminth fauna (three species at maximum), similar to other studies with lizards of this family in Brazil and that its parasite abundance is related to host snout-vent length, but not to the sex.
Keywords: lizard; nematode; parasitism; trematode